Archives of Lithuanian Latvian Families: the Case of the Dundurnieki Starkus - Ernestas Vasiliauskas (Acta Humanitarica Academiae Saulensis)
The article presents the Starkus (Latvian: Starks) family of farmers from the Daunorava (Latvian: Dundurmuiža, German: Donnerhof) Latvian dundurnieki community in Bertaučiai Village, Joniškis Parish, and the research sources on the subject matter. The research covers the following issues: (1) the 18th–19th century sources of family origin in memory preservation institutions, problem of the family origin and genealogy, the most well-known members of the family; (2) farms and sources of community demographics; (3) egodocuments and their specific features (photography collection, memoirs, diaries and letters) reflecting the economic, cultural, and social life of the community, reminiscences and genealogy of the family, kinship, and everyday activities. The sources used for the research are divided into the following categories: (1) documents in memory preservation institutions (documents of Daunorava Manor in the Latvian State Historical Archive, the Lithuanian State Historical Archives, and the Lithuanian State Central Archives: manor inventories from 1779–1797; census of souls from 1795–1834; farm censuses of 1846 and 1860; other documents from the first half of the 20th century); (2) egodocuments (1941–2007) of the Starkus Family: memoirs of the three generations of women – mother, daughter and granddaughter-niece; letters from Siberia (1948–1950); diaries of the secret agent, son-in-law Voldemaras Briedis (Voldemārs Briedis, 1944–1949); photographs from personal albums (from beginning of the 20th century to the 1970s, 285 pieces), with all digital copies stored in Aušros Museum in Šiauliai.